Lipids from the purple and white açaí (Euterpe oleracea Mart) varieties: nutritional, functional, and physicochemical properties - Santos, Orquídea Vasconcelos; Lemos, Yasmin Silva; da Conceição, Leyvison Rafael Viera; Teixeira-Costa, Bárbara E. (Frontiers in Nutrition, 2024)
This pioneer study aimed to compare the physicochemical, nutritional and thermal behaviour of vegetable oils obtained from two varieties of açaí (Euterpe oleracea), purple and white. Both açaí oils from white (WAO) and purple (PAO) variety, were obtained by using the conventional solid-liquid extraction, that resulted in oil yields ranging from 52-61%. WAO and PAO were analysed by their edibility quality parameters given the recommendations from Codex Alimentarius, their nutritional functionality indices as well as their composition of fatty acids and triglycerides content were estimated. Both oils showed low levels of acidity and peroxides, <1.8 mg KOH g -1 and <1.7 mEq kg - 1 , respectively, which are good indicators from their preservation status, agreeing with the food regulations. PAO and WAO showed differences among the fatty acids composition, mainly related to the content of monounsaturated fatty acids (MUFAs), which were 62.5% and 39.5%, respectively, mainly oleic acid. Regarding the polyunsaturated fatty acids (PUFAs), the WAO showed up to 23% of linoleic acid, whereas the PAO displayed up to 11% of it. These differences reflect on the values of the nutritional functionality indices, atherogenic (AI), thrombogenic (IT) and hypocholesterolemic/ hypercholesterolemic ratio (H/H). Both PAO and WAO showed low levels of AI and TI, and superior values of H/H compared to other oilseeds from the literature. These results indicate the nutritional properties of açaí oils regarding a potential cardioprotective effect when included in a regular dietary intake. The thermogravimetric behaviour and the evaluation of oxidation status by the infrared spectroscopy (FTIR) was also studied. Both açaí oils demonstrated higher thermal stability (with an onset temperature ranging from 344-350 °C) and low indications of oxidation status, since no chemical groups related to it were noted in the FTIR spectrum, which agrees with the determined acidity and peroxide content. Moreover, the FTIR analysis unveiled characteristic chemical groups related to the fatty acids and triglycerides, agreeing with the literature reports. These findings collectively contribute to a deeper comprehension of the nutritional, and functional properties between white and purple açaí oils, offering valuable insights into their potential health, food and industrial applications.